PELUANG DAN TANTANGAN OBLIGASI SYARI’AH DALAM PENERBITANNYA - RINA EL MAZA (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Islamic bond is a long-term securities issued by Islamic principles issuers to holders of Islamic bonds, which require the issuer to pay income to the holders of Islamic bonds in the form of profit sharing/margin/fee, as well as repay the bonds at maturity. So it can be seen from here that the contract of Islamic bonds instead of debts but the inclusion or investment. Under the provisions of DSN, the current Islamic bonds issued in Indonesia is still limited to two contract namely mudharabah and Ijarah. With the product of Islamic bonds is expected that the Muslims did not have doubts anymore if you want to invest in the capital market. There are many opportunities for Islamic bonds such as 1) Sukuk can be utilized to build the nation's economy and create a welfare society, 2) The investor has the alternative investments that are relatively safe and return her quite tempting, and 3) To strengthen the Indonesian economy and restrain bubble economy for will increase the portfolio of foreign currencies other than dollars. Barriers sukuk is 1) Socialization is not enough, AND 2) Opportunity cost is simply translated as